Patients Living With Breast Cancer During the Coronavirus Pandemic: The Role of Family Resilience, Coping Flexibility, and Locus of Control on Affective Responses - Brivio, Eleonora; Guiddi, Paolo; Scotto, Ludovica; Giudice, Alice V.; Pettini, Greta; Busacchio, Derna; Didier, Florence; Mazzocco, Ketti; Pravettoni, Gabriella (Frontiers in Psychology, 2021)
The Coronavirus (COVID-19) pandemic has strongly affected oncology patients. Many screening and treatment programs have been postponed or cancelled, and such patients also experience fear of increased risk of exposure to the virus (Casanova et al., 2020; Lewis, 2020). In many cases, locus of control, coping flexibility, and perception of a supportive environment, specifically family resilience, can allow for positive emotional outcomes for individuals managing complex health conditions like cancer. This study aims to determine if family resilience, coping flexibility, and locus of control can mitigate the negative affect of the pandemic and enhance positive affect in breast cancer patients. 181 female patients with breast cancer completed the Walsh’s Family Resilience Questionnaire, the Perceived Ability to Cope With Trauma Scale, the Positive-Negative Affect Schedule, and the Mini Locus of Control Scale. Results. Family resilience and internality of locus of control contribute significantly to positive affective responses. Family resilience is responsible for mitigating negative affect perceived during the pandemic, which is also enhanced by external locus of control. Evidence suggests that clinical psychologists should develop and propose programs to support oncology patients’ family resilience, coping flexibility, and internal locus of control, allowing for decreased stress and improved adaptability for effectively managing cancer treatment during the pandemic.